Effects of bariatric surgery on night eating and depressive symptoms : a prospective study - Pinto, Thisciane Ferreira (2017)
Background Night eating syndrome (NES) is characterized by a delayed pattern of food intake and is clinically defined by the presence of evening hyperphagia, nocturnal ingestion, morning anorexia, and sleep problems. Although most studies report an association of obesity, depressive mood, and NES, very little is known about the impact of bariatric surgery in the course of this syndrome, particularly in patients with depressive symptoms. Objectives To assess the effects of bariatric surgery on night eating and depressive symptoms. Setting Tertiary hospital, Brazil. Methods Sixty patients consecutively submitted to bariatric surgery were included in the study. Baseline depressive symptoms were assessed by the Beck Depression Inventory–Short Form (BDI-SF) and night eating by the Night Eating Questionnaire. Measurements were repeated postoperatively for comparison. Results Participants were predominantly female (M/F = 9/51). Mean (±SD) age was 34.7±9.2 years and body mass index was 46.04±7.52 kg/m². On average, BDI-SF scores improved after bariatric surgery (9.77±7.01 versus 4.70±4.60; P = .001). Patients with baseline depressive symptoms (BDI-SF>4), in contrast to those without, showed a significant improvement in Night Eating Questionnaire scores (16.03±7.73 versus 12.80±7.76; P = .01), despite a similar postoperative reduction in weight. Conclusion Bariatric surgery is associated with a reduction in depressive symptoms. After the surgical intervention, improvement of night eating can be observed predominantly in patients with preoperative depressive symptoms. These findings are consistent with the hypothesis of an important role of mood problems in NES.